Perancangan Robot Pembersih Lantai Berbasis Line Follower Dengan Kontrol Analog - Bernard Dehaan, Yeovan Naufal; Setiawan, Rudi; Daulay, Okky Freeza (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2024)
Analog Control-Based Floor Cleaning Robot is a technology in the form of a robot that follows a set line. One application of the line follower robot is a floor cleaning robot where the tool is used to clean the floor. At this Air Force Academy, floor cleaning still uses brooms so we innovated to use Analog Control Based Floor Cleaning Robots to shorten cleaning time. Analog Control-Based Floor Cleaning Robot will walk following a line measuring approximately 3 cm. where the line will be the movement path of this tool. In this final project, we used an infrared sensor to detect black lines as cleaning paths. With this tool, cadets who usually spend a longer time in carrying out cleaning become faster and more efficient so that they can carry out other activities.